Cowboys in India - Chambers, Simon (United Kngdom, 2009)
The film director embarks on journey to Orissa, India, where tribal people fight against multinational mining moguls from London. Aided by two endearing local guides, he searches for answers amongst conflicting allegations, as the truth becomes more and more elusive amidst other challenges.
Verzio Film Festival Submission
Keywords: Documentary films